I am Pusheen the cat - Belton, Claire (Gallery Books, 2019)
Pusheen is a pleasantly plump cat who has warmed hearts and tickled funny bones of millions worldwide with her signature GIF animated bops, bounces, and tail wiggles. Now, Pusheen is ready to make the leap from digital to print in her first comic collection! Learn what makes her purr and find out why millions of people have already fallen in love with this naughty, adorable kitty. Featuring some of the most popular stories from Pusheen's Tumblr and Facebook pages (plus a healthy serving of never before seen material), I Am Pusheen the Cat is a treat for cat lovers and comics fans alike.